1981
DOI: 10.1530/acta.0.0980222
|View full text |Cite
|
Sign up to set email alerts
|

Serum thyroglobulin in differentiated thyroid carcinoma: histological and metastatic classification

Abstract: Abstract. Serum thyroglobulin (tg) levels were measured in 112 patients with proved differentiated thyroid carcinoma (6 pre-operative, 32 post-operative and 74 in whom thyroidectomy was followed by radioiodine treatment). The tg levels were within the normal range in patients who had a residual mass in the neck region after surgery and who were in remission. The patients with metastases showed a wide range (undetectable to microgram quantities) of tg in circulation. The analysis of serum tg with respect to his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0
1

Year Published

1983
1983
2005
2005

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 0 publications
2
10
0
1
Order By: Relevance
“…Peculiar Tg levels could be seen in our patients with metastases. Like Shah et al [ 17] we observed higher Tg concentrations in the metastases of follicular thyroid carcinomas than in the papillary ones. The lower values in the latter were irrespective of the metastatic sites.…”
Section: Discussionsupporting
confidence: 83%
“…Peculiar Tg levels could be seen in our patients with metastases. Like Shah et al [ 17] we observed higher Tg concentrations in the metastases of follicular thyroid carcinomas than in the papillary ones. The lower values in the latter were irrespective of the metastatic sites.…”
Section: Discussionsupporting
confidence: 83%
“…Not all patients had total thyroidectomy or information missing Tubiana et al, 1985;Harvey et al, 1990;Schlumberger et al, 1991; Jadvar et al, 1998 Not all patients had radioiodine ablation or information missing Shlossberg et al, 1979;Shah et al, 1981;Echenique et al, 1982;Tubiana et al, 1985;Black et al, 1987;Schlumberger et al, 1988;Brendel et al, 1990;Black & Sheppard, 1991;Ruiz-Garcia et al, 1991;Dadparvar et al, 1993; Ladenson et al, 1997;Ruter et al, 1998; Ladenson, 2000;Ng et al, 2000;Sisson et al, 2000;Vitale et al, 2002 Tg cut-off values not indicated Dadparvar et al, 1993; Bejarano et al, 2000; Ladenson, 2000 Criteria for tumour missing Ng Tang Fui et al, 1979;Eber et al, 1980; Bednar et al, 1983;Schlumberger et al, 1988;Rubello et al, 1990;Grunwald et al, 1997; Ladenson et al, 1997;Roelants et al, 1997;Lin et al, 1998;Almeida-Filho et al, 2000;Fugazzola et al, 2002 Patients with Tg antibodies not excluded or information missing Bednar et al, 1983;Feldt-Rasmussen et al, 1983;Edmonds & Willis, 1988;Schlumberger et al, 1991;Meier et al, 1994;Feine et al, 1996;Roelants et al, 1997;Ruter et al, 1998;Grunwald et al, 1999;Seabold et al, 1999;de Klerk et al, 2000;Ng et al, 2000;Rubello et al, 2000;…”
Section: Appendixmentioning
confidence: 99%
“…Tg in the hypothyroid condition has been established as a sensitive tumor marker, 30,31 especially when measured by the most up-to-date assays. Detectable or elevated levels of thyroglobulin indicate persistent, recurrent or metastatic disease.…”
Section: Patientsmentioning
confidence: 99%